2023
DOI: 10.3390/ijms24097815
|View full text |Cite
|
Sign up to set email alerts
|

SerpinA3K Deficiency Reduces Oxidative Stress in Acute Kidney Injury

Abstract: We previously showed that SerpinA3K is present in urine from rats and humans with acute kidney injury (AKI) and chronic kidney disease (CKD). However, the specific role of SerpinA3K during renal pathophysiology is unknown. To begin to understand the role of SerpinA3K on AKI, SerpinA3K-deficient (KOSA3) mice were studied 24 h after inducing ischemia/reperfusion (I/R) and compared to wild type (WT) mice. Four groups were studied: WT+S, WT+IR, KOSA3+S, and KOSA3+IR. As expected, I/R increased serum creatinine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…On the contrary, some authors have found that under hypoxia conditions HIF-1α binds to FoxO3, which is thought to be a renoprotection factor after AKI, and subsequently inhibits the hydroxylation and degradation of FoxO3 [103]. SerpinA3K is another novel biomarker for the AKI to CKD transition in animal models, and knockout of serpinA3K resulted in higher FoxO3 expression with improved cellular responses to hypoxic injury, suggesting SerpinA3K's involvement in the renal oxidant response, HIF1α pathway, and cell apoptosis [104,105]. Studies exploring the effectiveness of PHD inhibitors in renal injury highlighted the positive impact of HIFs on renal fibrosis [106].…”
Section: Hypoxiamentioning
confidence: 99%
“…On the contrary, some authors have found that under hypoxia conditions HIF-1α binds to FoxO3, which is thought to be a renoprotection factor after AKI, and subsequently inhibits the hydroxylation and degradation of FoxO3 [103]. SerpinA3K is another novel biomarker for the AKI to CKD transition in animal models, and knockout of serpinA3K resulted in higher FoxO3 expression with improved cellular responses to hypoxic injury, suggesting SerpinA3K's involvement in the renal oxidant response, HIF1α pathway, and cell apoptosis [104,105]. Studies exploring the effectiveness of PHD inhibitors in renal injury highlighted the positive impact of HIFs on renal fibrosis [106].…”
Section: Hypoxiamentioning
confidence: 99%